2016
DOI: 10.1007/s00220-016-2665-0
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Striped Ground States in Ising Models with Competing Interactions

Abstract: Abstract:We consider Ising models in two and three dimensions, with short range ferromagnetic and long range, power-law decaying, antiferromagnetic interactions. We let J be the ratio between the strength of the ferromagnetic to antiferromagnetic interactions. The competition between these two kinds of interactions induces the system to form domains of minus spins in a background of plus spins, or vice versa. If the decay exponent p of the long range interaction is larger than d + 1, with d the space dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 41 publications
6
57
0
Order By: Relevance
“…In the continuous setting, to our knowledge this is the first example of a model with local/nonlocal terms in competition such that the functional is invariant under permutation of coordinates and the minimizers display a pattern formation which is one-dimensional. Such behaviour for a smaller range of exponents in the discrete setting was already shown in [1].where J is a positive constant, Per 1 is the 1-perimeter and | · | 1 is the 1-norm and K 1 (ζ) := 1 (|ζ|1+1) p . The perimeter term acts as short-range attracting force and the nonlocal term as repulsive long-range force.…”
supporting
confidence: 64%
“…In the continuous setting, to our knowledge this is the first example of a model with local/nonlocal terms in competition such that the functional is invariant under permutation of coordinates and the minimizers display a pattern formation which is one-dimensional. Such behaviour for a smaller range of exponents in the discrete setting was already shown in [1].where J is a positive constant, Per 1 is the 1-perimeter and | · | 1 is the 1-norm and K 1 (ζ) := 1 (|ζ|1+1) p . The perimeter term acts as short-range attracting force and the nonlocal term as repulsive long-range force.…”
supporting
confidence: 64%
“…A difficulty with our Peierls argument is to control the change in the number of loops when erasing a contour. We find it convenient to condition on the configuration of external contours away from (x, 0); a similar idea was used in [14]. This gives a domain with complicated shape, but this is not a problem.…”
Section: Contour Representationmentioning
confidence: 99%
“…The research reported in this article was completed during the workshop Many-Body Quantum Systems and Effective Theories at the Mathematisches Forschungsinstitut Oberwolfach, September [11][12][13][14][15][16][17] 2016. We thank the organizers and the institute for the great hospitality and the stimulating program.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Any relation of the present work to [9,28] is unclear, since the measures under consideration are different. Different isoperimetric problems exhibiting "crystallization" (or the optimality of sets consisting of parallel stripes) have been studied in, for example [7,12,14,15,33], though these studies have typically focused only on n = 2 or n = 3.…”
Section: Other Related Workmentioning
confidence: 99%
“…Different isoperimetric problems exhibiting “crystallization” (or the optimality of sets consisting of parallel stripes) have been studied in, for example , though these studies have typically focused only on n = 2 or n = 3.…”
Section: Introductionmentioning
confidence: 99%